Building construction - Varghese, P. C. (PHI Learning, 2007)
This book, a companion volume to the author's book on "Building Materials", explains the basics of building construction practices in an accessible style. It discusses in detail every element of building construction from start to the finish - from site preparation to provision of services (such as water supply, drainage and electricity supply). Besides, the text describes acoustics and maintenance of buildings, which are important considerations in construction of buildings.This book is primarily designed as an introductory textbook for undergraduate students of civil engineering as well as those pursuing diploma courses in civil engineering and architecture. Practicing engineers and any person who has a keen interest in the construction and maintenance of his/her own building will also find the book very helpful.Separate appendix is given to discuss earthquake-resistant design of buildings. Review questions provided at the end of each chapter enable the readers recapitulate the topics. The references to IS codes and standards make the text suitable for further study and field use. Because of the lecture-based presentation of the subject, the text will be of considerable benefit for the young teachers for their classroom lectures.